PENGARUH AUDIT DELAY, OPINI AUDIT, DAN AUDIT TENURE TERHADAP PERGANTIAN KANTOR AKUNTAN PUBLIK (KAP) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2010-2015 - Muhammad Luthfi; Dian Apita Sari (Jurnal Ilmiah Akuntansi Rahmaniyah, 2019)
This reserach aims to analyze the influence of Audit Delay, Opin Audit and Audit Tenure on changes to Public Accounting Firm (KAP) in Indonesia. Some previous research on the change of KAP looks different results.Therefore, another study was conducted to re-examine the theory of the change of KAP.Data collection method used in this research is purposive sampling, that is sample collection method based on the criteria of the research objectives. Pursuant to purposive sampling method, total sample obtained in this research is 240 samples from manufacturing company listed in Indonesia Stock Exchange (BEI) during period 2010-2015. Hypothesis testing in this study was done by using logistic regression method (logistic regression) in the application of SPSS 22 program.The result of the research shows that audit opinion influences significantly to the change of KAP whereas, audit delay and audit tenure does not significantly influence the change of KAP.